Change in Lifestyle Behaviors After Preconception Care: A Prospective Cohort Study. Issue 1 (January 2021) - Sijpkens, Meertien K.; van Voorst, Sabine F.; Rosman, Ageeth N.; de Jong-Potjer, Lieke C.; Denktaş, Semiha; Koch, Birgit C.P.; Bertens, Loes C.M.; Steegers, Eric A.P.
Purpose: To evaluate the effects of preconception care (PCC) consultations by change in lifestyle behaviors. Setting and Intervention: Women in deprived neighborhoods of 14 Dutch municipalities were encouraged to visit a general practitioner or midwife for PCC. Sample: The study included women aged 18 to 41 years who had a PCC consultation. Design: In this community-based prospective cohort study, we assessed initiation of folic acid supplementation, cessation of smoking, alcohol consumption, and illicit drug use. Measures: Self-reported and biomarker data on behavioral changes were obtained at baseline and 3 months later. Analysis: The changes in prevalence were assessed with the McNemar test. Results: Of the 259 included participants, paired analyses were available in 177 participants for self-reported outcomes and in 82 for biomarker outcomes. Baseline self-reported prevalence of no folic acid use was 36%, smoking 12%, weekly alcohol use 22%, and binge drinking 17%. Significant changes in prevalence toward better lifestyle during follow-up were seen for folic acid use (both self-reported, P < .001; and biomarker-confirmed, P = .008) and for self-reported binge drinking ( P = .007). Conclusion: Our study suggests that PCC contributes to initiation of folic acid supplementation and cessation of binge drinking in women who intend to become pregnant. Although based on a small sample, the study adds to the limited body of evidence regarding the benefits of PCC in improving periconception health.